A new WDM Application Response Time in WLAN Network and Fixed WiMAX using Distributed - Nisar, K. (IEEE Computer Society, 2014)
Worldwide Interoperability for Microwave Access (WiMAX) and Wireless LAN (WLAN) has emerged as a promising solution for last mile access technology to provide high speed internet access in the residential as well as small and medium sized enterprise sectors. Application Response Time is the key performance measure in WiMAX and WLAN Network Quality of Service (QoS). The WiMAX network does not provide sufficient QoS with respect to Application Response Time. Wavelength Division Multiplexing (WDM) has emerged as the promising technology to meet the ever-increasing demand for bandwidth In this paper, we developed a Distributed Client-Server Model to improve QoS with respect to Application Response Time in the Fixed WiMAX and WLAN Network in order to enhance the services that are provided to the end users. The new distributed Client-Server model was simulated in OPNET modeler 16.0 with multiple Base Stations (BSs), Subscribers Stations (SSs) and some Server BSs selected by the Nearest Neighborhood Algorithms using Orthogonal Frequency Division Multiplexing (OFDM) techniques and compared with the existing Centralized model using Frequency Division Multiplexing (FDM) techniques. The simulation results obtained for the application response time of the proposed Client-Server model show an improvement in network performance. Â© 2014 IEEE.